Validation of a combined autosomal/Y-chromosomal STR approach for analyzing typical biological stains in sexual-assault cases. (November 2015) - Purps, Josephine; Geppert, Maria; Nagy, Marion; Roewer, Lutz
Highlights: We report success rates of a combined autosomal/Y chromosomal workflow for stain analysis in a wide spectrum of sexual assault cases. In a large retrospective case study we reviewed 287 cases with 2077 stains. Our investigation revealed that the Y-STR analysis adds up to 21% complete, single-source profiles on top of the informative autosomal STR profiles. The detection of multiple male donorship was about three times more likely with Y chromosomal than with autosomal STR profiling. One of ten cases would have been left inconclusive without parallel Y-STR analysis. Abstract: DNA testing is an established part of the investigation and prosecution of sexual assault. The primary purpose of DNA evidence is to identify a suspect and/or to demonstrate sexual contact. However, due to highly uneven proportions of female and male DNA in typical stains, routine autosomal analysis often fails to detect the DNA of the assailant. To evaluate the forensic efficiency of the combined application of autosomal and Y-chromosomal short tandem repeat (STR) markers, we present a large retrospective casework study of probative evidence collected in sexual-assault cases. We investigated up to 39 STR markers by testing combinations of the 16-locus NGMSElect kit with both the 23-locus PowerPlex Y23 and the 17-locus Yfiler kit. Using this dual approach we analyzed DNA extracts from 2077 biological stains collected in 287 cases over 30 months. To assess the outcome of the combined approach in comparison to stand-alone autosomal analysis we evaluated informative DNA profiles. Our investigation revealed that Y-STR analysis added up to 21% additional, highly informative (complete, single-source) profiles to the set of reportable autosomal STR profiles for typical stains collected in sexual-assault cases. Detection of multiple male contributors was approximately three times more likely with Y-chromosomal profiling than with autosomal STR profiling. In summary, 1/10 cases would have remained inconclusive (and could have been dismissed) if Y-STR analysis had been omitted from DNA profiling in sexual-assault cases.